Pengaruh Preventive Maintance dan Breakdown Maintance terhadap Kelancaran Proses Produksi - Ajmal Eka Mulya Mulya; Rita Tri Yusnita; Suci Putri Lestari (Jurnal Ekonomi & Bisnis, 2022)
This study aims to determine the simultaneous and partial effect of preventive maintenance and breakdown maintenance on the smooth production process (a case study at the Marrivosa Rubber Sandal Cigantang Company, Tasikmalaya City. The research method used is survey and quantitative methods. The sample used is random sampling. The data used are primary data in the form of preventive maintenance cost data, damage maintenance cost data, and production target data for the last 5 years, namely in the 2017-2021 period. The analytical tool used in this study is multiple regression using SPSS 16. The results of the study shows that simultaneously preventive maintenance and breakdown maintenance have a significant effect on the smoothness of the production process Partially, preventive maintenance and breakdown maintenance have a significant effect on the smoothness of the production process.